2022
DOI: 10.1007/s44154-022-00067-w
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ signaling in plant manganese uptake: CPK21/23 kinases phosphorylate and activate manganese transporter NRAMP1

Abstract: This brief article highlights the results of Fu et al. (Proc Natl Acad Sci USA 119:e2204574119, 2022), who recently found that manganese (Mn) deficiency triggers long-lasting multicellular Ca2+ oscillations in the elongation zone (EZ) of Arabidopsis roots and revealed a Ca2+-CPK21/23-NRAMP1 axis as an important mechanism for plant tolerance and adaptation to low Mn.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The induction of TaN-RAMP3 by Mn deficiency implies precise transcriptional regulation. In addition, recent studies have shown that NRAMP1 was phosphorylated by the protein kinases CPK21/23 and CIPK23 in Arabidopsis (Fu et al 2022;Zhang et al 2023a;Huang 2022), The 24th residue of TaNRAMP3 protein is also serine, which corresponds to the Ser22 of AtNRAMP1, indicating that TaNRAMP3 may also undergo phosphorylated. Therefore, exploring the transcription factors and protein kinases that regulate TaNRAMP3 will be one of our future research.…”
Section: Discussionmentioning
confidence: 98%
“…The induction of TaN-RAMP3 by Mn deficiency implies precise transcriptional regulation. In addition, recent studies have shown that NRAMP1 was phosphorylated by the protein kinases CPK21/23 and CIPK23 in Arabidopsis (Fu et al 2022;Zhang et al 2023a;Huang 2022), The 24th residue of TaNRAMP3 protein is also serine, which corresponds to the Ser22 of AtNRAMP1, indicating that TaNRAMP3 may also undergo phosphorylated. Therefore, exploring the transcription factors and protein kinases that regulate TaNRAMP3 will be one of our future research.…”
Section: Discussionmentioning
confidence: 98%
“…As a crucial signal molecule in eukaryotes, Ca 2+ signals have a significant impact on plant growth and development as well as how plants adapt to biotic and abiotic stresses (Luan & Wang, 2021; Chong et al ., 2022; Gorgues et al ., 2022; Köster et al ., 2022; Zhang et al ., 2022). CPKs act as Ca 2+ sensors, not only detecting these signals but also transducing them into phosphorylation events that regulate downstream targets (Boudsocq & Sheen, 2013; Huang, 2022; Liang & Zhang, 2022; Z. Wang et al ., 2023). BOR1 is a crucial protein for the efficient translocation of B from the root to the xylem under B‐deficient conditions (Takano et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%